Սամցխե-Ջավախքի ու Ծալկայի պատմաքաղաքական և ժողովրդագրական իրավիճակը - Դ. Տ. Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
В разные исторические периоды Джавахк входил в состав Армении или в состав соседних государств. На протяжении определенного исторического отрезка он являл собой независимую государственную единицу. В настоящее время злободневной задачей является демографическая ситуация в Джавахке. In different periods of its history, Javakhk was either a part of Armenia or neighbouring states. It was also an independent state entity fro a certain period. At present, one of the most important issues of Javakhk is the demographic situation of the region.
Keywords: History; Political Science; Demography; Population; Vital Events; D History; H Social Sciences; J Political Science